Treating Multiple Incident Post-Traumatic Stress Disorder (PTSD) in an Inner City London Prison: The Need for an Evidence Base. Issue 1 (20th February 2015) - Campbell, Catherine A.; Albert, Idit; Jarrett, Manuela; Byrne, Majella; Roberts, Anna; Phillip, Patricia; Huddy, Vyv; Valmaggia, Lucia
Abstract : Background: Mental health problems have been found to be more prevalent in prison populations, and higher rates of post-traumatic stress disorder (PTSD) have been found in sentenced populations compared to the general population. Evidence-based treatment in the general population however has not been transferred and empirically supported into the prison system.Aims: The aim of this manuscript is to illustrate how trauma focused work can be applied in a prison setting.Method: This report describes a two-phased approach to treating PTSD, starting with stabilization, followed by an integration of culturally appropriate ideas from narrative exposure therapy (NET), given that the traumas were during war and conflict, and trauma-focused cognitive behavioural therapy (TF-CBT).Results : PTSD and scores on paranoia scales improved between start and end of treatment; these improvements were maintained at a 6-month follow-up.Conclusion : This case report 1 illustrates successful treatment of multiple incident PTSD in a prison setting using adaptations to TF-CBT during a window of opportunity when individuals are more likely to be free from substances and live in relative stability. Current service provision and evidence-based practice for PTSD is urgently required in UK prisons to allow individuals to engage in opportunities to reduce re-offending, free from mental health symptoms.